Epidemiological pattern of cleft lip and palate under Rashtriya Bal Swasthya Karyakram project in the state of Bihar: A cross-sectional hospital-based study - Shria Datta; Veena Kumari Singh (Journal of Family Medicine and Primary Care)
Purpose: There is a paucity of literature on the incidence and distribution of cleft lip and palate cases in the population of Bihar leading to an unmeasured gap in the status of cleft patients in this part of the country. The present study assessed the pattern of cleft cases in the community reported at the largest cleft center in the state under Rashtriya Bal Swasthya Karyakram (RBSK). Methodology: The study was a questionnaire-based, cross-sectional study conducted over one month at a tertiary care center in Bihar. It included all patients with cleft lip and palate, below the age of 5 years, either isolated or combined, attending the OPD or admitted to the ward in the plastic surgery department. Results: The demographic distribution of cleft lip patients included 16% cleft lip, 6% cleft lip with alveolus, 2% microform, 46% cleft palate, and 30% cleft lip with cleft palate. Bilateral cases contributed to 42% of all cases. Male to female ratio was 3:2 with a ratio of 5:3 in cleft lip, 2:1 in cleft lip with alveolus, 0:1 in microform, 12:11 in cleft palate, and 11:4 in cleft lip with palate patients, respectively. Conclusion: The incidence and distribution of cleft lip and palate were found to be similar to the studies done in other parts of India. Registration of cleft cases under the RBSK project of the central government has led to affordable treatment for poor patients in the state of Bihar.